2019
DOI: 10.3390/app9071487
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrashort-Term Net Load Forecasting Model Based on Phase Space Reconstruction and Deep Neural Network

Abstract: Recently, a large number of distributed photovoltaic (PV) power generations have been connected to the power grid, which resulted in an increased fluctuation of the net load. Therefore, load forecasting has become more difficult. Considering the characteristics of the net load, an ultrashort-term forecasting model based on phase space reconstruction and deep neural network (DNN) is proposed, which can be divided into two steps. First, the phase space reconstruction of the net load time series data is performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…During the heuristics, we gradually increase the number of hidden layers until the predicted value is obviously overfitting, and then gradually reduce the number of hidden layers to minimize the model error, thereby determining the optimal number of hidden layers. In this paper, through multiple experiments, the model performance is best when the number of hidden layers is 4 and the neurons of each hidden layer are 6, 4, 3, and 2, respectively [34]. The activation function of hidden neurons uses the tanh function.…”
Section: ( ) ( ) ( )mentioning
confidence: 99%
“…During the heuristics, we gradually increase the number of hidden layers until the predicted value is obviously overfitting, and then gradually reduce the number of hidden layers to minimize the model error, thereby determining the optimal number of hidden layers. In this paper, through multiple experiments, the model performance is best when the number of hidden layers is 4 and the neurons of each hidden layer are 6, 4, 3, and 2, respectively [34]. The activation function of hidden neurons uses the tanh function.…”
Section: ( ) ( ) ( )mentioning
confidence: 99%
“…The results showed that the hybrid forecasting method offers better accuracy and stability than the single prediction methods. Additionally, Mei et al [15] developed an ultrashort-term forecasting model based on the phase space reconstruction and deep neural network (DNN) by considering the characteristics of the net load. The performance of this model was verified using real data, with superior accuracy in forecasting the net load under high PV penetration rates and different weather conditions.…”
Section: Performance Assessmentmentioning
confidence: 99%
“…Where ε is the learning rate, which takes the value of 0.8 in this paper, and the superscript k represents the k-th iteration. In this paper, the LM (Levenberg-Marquardt) BP algorithm [31] is used to replace the traditional BP algorithm to fine-tune the DBN. Compared with the traditional BP algorithm, the LMBP algorithm has faster convergence speed and higher convergence reliability, and is more suitable for training neural networks with many hidden layers and neurons.…”
Section: Dbn Based On Levenberg-marquardt Backpropagation (Lmbp) Algomentioning
confidence: 99%